Dog bite injuries a preventable hazard?. (1st March 2011) - Butcher, R; De Keuster, T
Abstract : Estimates indicate 1.5% of the population is bitten by a dog annually (though probably 50% of bites remain unreported), and that the incidence is increasing. However, dogs are popular pets associated with scientifically proven health and social benefits for their owners and their families. It is important to devise bite prevention strategies that preserve these benefits while reducing the risk of injuries. Contrary to the popular view that the problem is restricted to a few so-called dangerous breeds, evidence indicates that most bites occur within the home, most often in young children bitten by a familiar dog. These incidents therefore reflect a significant cause of accidents to children in the home that can be prevented. Within the home, 86% of the bites appear to be triggered by a dog/child interaction initiated by the child. However, the majority of bites occurring in public places happen without previous interaction from the victim. The tendency of a dog to bite depends on multiple interacting factors including those related to the individual dog and the individual victim, but importantly influenced by the sociocultural context. In conclusion, more research is needed on the epidemiology of bites to help identify the most appropriate prevention strategies. These should focus on the context rather than simply on dog attack records. The research and future implementation of strategies will require coordination and involvement of all major stakeholders, but it seems clear education (of both healthcare professionals and general public) will be the key.